Response of the peatland carbon dioxide sink function to future climate change scenarios and water level management - Salimi, Shokoufeh; Berggren, Martin; Scholz, Miklas (Global change biology, 2021)
Stress factors such as climate change and drought may switch the role of temperate peatlands from carbon dioxide (CO2) sinks to sources, leading to positive feedback to global climate change. Water level management has been regarded as an important climate change mitigation strategy as it can sustain the natural net CO2 sink function of a peatland. Little is known about how resilient peatlands are in the face of future climate change scenarios, as well as how effectively water level management can sustain the CO2 sink function to mitigate global warming. The authors assess the effect of climate change on CO2 exchange of south Swedish temperate peatlands, which were either unmanaged or subject to water level regulation. Climate chamber simulations were conducted using experimental peatland mesocosms exposed to current and future representative concentration pathway (RCP) climate scenarios (RCP 2.6, 4.5 and 8.5). The results showed that all managed and unmanaged systems under future climate scenarios could serve as CO2 sinks throughout the experimental period. However, the 2018 extreme drought caused the unmanaged mesocosms under the RCP 4.5 and RCP 8.5 switch from a net CO2 sink to a source during summer. Surprisingly, the unmanaged mesocosms under RCP 2.6 benefited from the warmer climate, and served as the best sink among the other unmanaged systems. Water level management had the greatest effect on the CO2 sink function under RCP 8.5 and RCP 4.5, which improved their CO2 sink capability up to six and two times, respectively. Under the current climate scenario, water level management had a negative effect on the CO2 sink function, and it had almost no effect under RCP 2.6. Therefore, the researchers conclude that water level management is necessary for RCP 8.5, beneficial for RCP 4.5 and unimportant for RCP 2.6 and the current climate. Drought may switch the role of wetlands from carbon dioxide (CO2) sinks to sources. Water level management of temperate peatlands had the greatest effect on the CO2 sink function under representative concentration pathway (RCP) 8.5 and RCP 4.5, which improved their CO2 sink capability up to six and two times, respectively. Under the current climate, water level management had a negative effect on the CO2 sink function, and it had almost no effect under RCP 2.6. So, water level management is necessary for RCP 8.5, beneficial for RCP 4.5 and unimportant for RCP 2.6 and the current climate.